2006
DOI: 10.1128/jcm.44.5.1681-1685.2006
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, Risk Factors, and Prognosis of Candida parapsilosis Bloodstream Infections: Case-Control Population-Based Surveillance Study of Patients in Barcelona, Spain, from 2002 to 2003

Abstract: Candida parapsilosis has emerged as an important yeast species causing fungemia. We describe the incidence and epidemiology of C. parapsilosis fungemia. Data from active population-based surveillance in Barcelona, Spain, from January 2002 to December 2003 were analyzed. We focused on 78 episodes of C. parapsilosis fungemia, and we compared them with 175 Candida albicans controls. C. parapsilosis accounted for 23% of all fungemias. The annual incidences were 1 episode per 10 5 patients, 1.2 episodes per 10 4 di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
167
2
15

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 218 publications
(196 citation statements)
references
References 40 publications
12
167
2
15
Order By: Relevance
“…Although Candida albicans represents the most frequent aetiological agent of candidaemia globally, the expanding role of C. parapsilosis reinforces the necessity of monitoring the incidence and susceptibility profile of this agent (Almirante et al, 2006;Trofa et al, 2008). Genetic heterogeneity of C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis has been demonstrated using RAPD analysis, detection of nucleotide variations in the internal transcribed spacer gene and other techniques (Lida et al, 2005;Tavanti et al, 2005Tavanti et al, , 2007Lasker et al, 2006;van Asbeck et al, 2008;Tay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Although Candida albicans represents the most frequent aetiological agent of candidaemia globally, the expanding role of C. parapsilosis reinforces the necessity of monitoring the incidence and susceptibility profile of this agent (Almirante et al, 2006;Trofa et al, 2008). Genetic heterogeneity of C. parapsilosis sensu stricto, C. orthopsilosis and C. metapsilosis has been demonstrated using RAPD analysis, detection of nucleotide variations in the internal transcribed spacer gene and other techniques (Lida et al, 2005;Tavanti et al, 2005Tavanti et al, , 2007Lasker et al, 2006;van Asbeck et al, 2008;Tay et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent studies have further reported C. parapsilosis to be the predominant species causing neonatal infections at intensive care units (ICU), threatening especially low birth weight infants, with significant neonatal mortality [7,[22][23][24]. Additionally, diverse adult patients with diminished immunity are also at risk [25][26][27][28]. Further risk factors include the use of lipid rich parenteral nutrition and prolonged use of implanted devices, as C. parapsilosis readily forms and maintains stable biofilms on the surfaces of commonly used medical equipments [29].…”
Section: Introductionmentioning
confidence: 99%
“…[19] Although C. parapsilosis is less virulent, but under certain conditions (IV catheters, high IV glucose concentrations) virulence may increase many folds and it is relatively difficult to eradicate this organism. [20] Outbreaks of C. parapsilosis BSI in NICUs have been previously reported in the study of Almirante B et al(2006). [21] C. parapsilosis and C. glabrata are an emerging fungal pathogen and the major threat for neonates in NICU as it frequently colonizes the hands of HCW, has high affinity for intravascular devices, and parenteral nutrition.…”
Section: Discussionmentioning
confidence: 99%
“…[20] Outbreaks of C. parapsilosis BSI in NICUs have been previously reported in the study of Almirante B et al(2006). [21] C. parapsilosis and C. glabrata are an emerging fungal pathogen and the major threat for neonates in NICU as it frequently colonizes the hands of HCW, has high affinity for intravascular devices, and parenteral nutrition. [22] C. tropicalis is the second leading cause of candidemia in adults,but is quite infrequent among neonates.…”
Section: Discussionmentioning
confidence: 99%